Agricultura orgânica como alternativa para a agricultura familiar e como parte de uma política de desenvolvimento sustentável no Ceará - Santos, Felipe Bezerra dos (2012)
The study aims to propose the use of organic farming as a basis for strengthening family farming, and suggests recommendations for an agricultural policy that contributes to a sustainable development for the State of Ceará. The reason lies in the fact that family farms present many challenges in the way they’re being performed over the years, and achieving socioeconomic and environmental sustainability by this means has become increasingly distant, especially in Ceará – that has almost 90% of its territory covered by semiarid regions, and is home to a significant portion of the population. On the other hand, organic production would reduce or even correct the adverse effects caused by the misuse of agricultural techniques, excessive in pesticides, that damage the soil and the health of those who handle them. For the purpose, the research was based on a theoretical framework about family farming, economic development, regional development and sustainable development, and on the concepts of environmentally friendly production, on which organic farming is grounded. The methodology used was mainly bibliographic research, based on the collection available in books, scientific articles, government bodies and official statistical agencies. A search on the public policies applied to agriculture in four decades was conducted and the main source for the subject’s statistics was the IBGE. But a research was also conducted on the main sources related to the topic, among these sources the Ministry of Agriculture, Animal Husbandry and Supply (MAPA) stands out. It’s worth mentioning here the difficulty in obtaining data on the actual size of organic production in Brazil, especially in Ceará, and the few existing statistics are not updated. The study shows that in 40 years of policies and investments addressed to the rural sector, still 17% of this population lives in extreme poverty, suggesting that the traditional means of cultivation employed aren’t efficient in reaching the desired sustainability. It highlights the perverse effects of traditional family farming practices operationalized through inappropriate land use, especially the use of slash-and-burn, becoming in some areas of Ceará’s hinterlands with a high degree of desertification. Finally, the study makes recommendations to create a sustainable policy for family farming, focused on organic farming, since this is the most viable solution for the State of Ceará, given its geoeconomic characteristics. Besides, the demand for ecologically clean products is growing every day, making organic farming a potential to be explored.